Advances in the detection of biomarkers for ischemic stroke - Ying Liang; Juan Chen; Yue Chen; Yaoyao Tong; Linhao Li; Yuan Xu; Shimin Wu (Frontiers in Neurology)
Ischemic stroke is a leading cause of mortality and morbidity globally. Prompt intervention is essential for arresting disease progression and minimizing central nervous system damage. Although imaging studies play a significant role in diagnosing ischemic stroke, their high costs and limited sensitivity often result in diagnostic and treatment delays. Blood biomarkers have shown considerable promise in the diagnosis and prognosis of ischemic stroke. Serum markers, closely associated with stroke pathophysiology, aid in diagnosis, subtype identification, prediction of disease progression, early neurological deterioration, and recurrence. Their advantages are particularly pronounced due to their low cost and rapid results. Despite the identification of numerous candidate blood biomarkers, their clinical application requires rigorous research and thorough validation. This review focuses on various blood biomarkers related to ischemic stroke, including coagulation and fibrinolysis-related factors, endothelial dysfunction markers, inflammatory biomarkers, neuronal and axonal injury markers, exosomes with their circular RNAs and other relevant molecules. It also summarizes the latest methods and techniques for stroke biomarker detection, aiming to provide critical references for the clinical application of key stroke biomarkers.